Panama : First Review Under the Arrangement Under the Precautionary and Liquidity Line-Press Release; Staff Report; and Statement by the Executive Director for Panama. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
Macroeconomic vulnerabilities have declined since the peak of the COVID-19 pandemic in 2020. The economy is expected to rebound swiftly in 2021 as activities return to normality and the population is increasingly vaccinated. External imbalances are contained. The fiscal position is gradually consolidated as the authorities remain committed to the revised fiscal rule, which will ensure a declining path for the NFPS debt. The outlook remains subject to elevated risks, including uncertainties arising from possible more contagious variants of the COVID-19 virus. Domestic risks include setbacks in implementing the FATF action plan to exit the grey list, delays in fiscal consolidation, and a prolonged pandemic that could exacerbate socioeconomic hardship and derail economic policies and the recovery.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Panama